2011
DOI: 10.1016/j.apsusc.2010.12.044
|View full text |Cite
|
Sign up to set email alerts
|

An interface study of crystalline Fe/Ge multilayers grown by molecular beam epitaxy

Abstract: a b s t r a c tFe/Ge multilayers were grown on single crystal Ge(0 0 1) substrates by molecular beam epitaxy. The structural, electronic and magnetic properties of Fe/Ge have been studied. The analysis shows that Fe grows in a layer-by-layer epitaxial growth mode on Ge(0 0 1) substrates at 150 • C and no intermixing has been observed. Growth of a crystalline Ge film at 150 • C on a single crystal Fe film has been observed. At this temperature Ge films grow by means of the island growth mode according to reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
(15 reference statements)
1
5
0
Order By: Relevance
“…So the interfacial roughness will be decreased and the upper interface on NiFe layer will be smoother. Although the exchange bias coupling will be weaker after the Cu insertion, the decreased exchange bias field with smoother interface not only provides the pinning direction for magnetic moments, but also can make the magnetic moments rotate more consistently with the decreased rotation frustration [11,[21][22][23].…”
Section: Resultsmentioning
confidence: 97%
“…So the interfacial roughness will be decreased and the upper interface on NiFe layer will be smoother. Although the exchange bias coupling will be weaker after the Cu insertion, the decreased exchange bias field with smoother interface not only provides the pinning direction for magnetic moments, but also can make the magnetic moments rotate more consistently with the decreased rotation frustration [11,[21][22][23].…”
Section: Resultsmentioning
confidence: 97%
“…We must stress here that this is the first time that ferromagnetism is detected in a Ge-rich Fe–Ge surface compound. Also, along the [110] in-plane direction the ferromagnetism is quite robust, since the coercitive field is about 230 Oe, much larger than the reported coercitive fields for Fe grown on Ge [16,17,18,19,20,21]. The measured coercitive fields for FeGe(001) largely exceed that of metal Fe or even of reacted Fe on Si(001) [10,11].…”
Section: Resultsmentioning
confidence: 99%
“…Comparatively, there are fewer efforts to work on Fe–Ge systems, although iron is a better magnet than manganese. Efforts are continuously concentrated in the synthesis of well ordered and low intermixing Fe layers on Ge(001) [ 4 , 16 , 17 , 18 , 19 , 20 , 21 ], (011) [ 22 ] or (111) surfaces [ 23 , 24 ]. Basically, most Fe layers are reported to be ferromagnetic with an onset of ferromagnetism at few (3–5) atomic iron layers [ 19 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tuning the size distribution and spatial ordering of these structures remains a continuing challenge. Metal/metal, metal/ceramic and ceramic/ceramic are type of the model materials used in the investigation of the selforganization of nanostructures in semiconductor and mechanical heterostructures [3][4][5]. In the case of iso-structural multilayers (e.g., NaClfcc-NaClfcc), molecular dynamics (MD) simulations have shown that the peak strength is set by coherency stresses which in turn are determined by elastic modulus and lattice parameter mismatch [6].…”
Section: Introductionmentioning
confidence: 99%